Gambaran Pelaksanaan Toilet Training oleh Guru di PAUD Duta School Gunung Pangilun Padang - Eka Putri Natasya; Wirdatul Aini; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research is motivated by the ability of early child in good toilet training activity. The purpose of this research is to describe about (1) describe the management of the learning environment (2) describe the learning media (3) describe the learning method. The type of this research is descriptive quantitative, population in research amount to 30 people. Samples were taken as much as 65%. The number of samples is 20 people. The sampling technique uses cluster random sampling. Data collection techniques used are questionnaires, while data collection tools using questionnaires. Data analysis techniques using the formula percentage. From the research result that (1) management of learning environment (class) on toilet training implementation in good category, (2) instructional media used by teacher in toilet training implementation in good category, (3) learning method used in toilet training implementation in category good. Suggestions from this research so that the management of learning environment, learning media and learning methods on the implementation of toilet training can be improved by the school.Keywords: Implementation, Toilet Training